THE RIGHT TO THE INTELLIGENT CITY AND THE VULNERABLE CITIZENSHIP. NOTES FOR A SOCIOTECHNICAL CRITIQUE OF AI (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The "legal underdetermination" () of smart cities leads one to speak of cities with vulnerable citizenship. As noted in the fields of AI ethics, the implementation of predictive algorithms in smart cities exacerbates the vulnerability of the citizen-user, subject not only to privacy restrictions, but to processes of dispossession and forms of epistemic injustice (). Correlatively, the normative foundations of identity, freedom, autonomy and responsibility are undermined. Taking a cue from Stiegler's pharmacological perspective and David Berry's work on digital infrasomatisation and the social right to explainability, the paper proposes a socio-technical reflection on the vulnerability of citizenship.
Keywords: Algorithmic Governmentality; Pharmacology; Smartness; Epistemic injustice; Infrasomatisation